SENI SINGIRAN DALAM RITUAL TAHLILAN PADA MASYARAKAT ISLAM TRADISIONAL JAWA - -, Kusnadi (Imaji: Jurnal Seni dan Pendidikan Seni, 2015)
The phenomenon of Singiran in tahlilan is typically Javanese. Singiran is a form of Javanese singing art (tembang) performed in the middle of tahlilan ritual, especially when tahlil words are being recited. The aims of this writing are (1) to describe the form of Singiran song found among the society of Ngemplak Nganti, Sendangadi Mlati Sleman, and (2) to describe the function of Singiran art in the context of Islamic traditional Javanese culture. The form of Singiran song is typically different from other genres of Javanese songs, such as those in karawitan, pedalangan and santiswara/ larasmadya. The laras (pitch) used is both pelog (seven-tone gamelan scale) and slendro five-tone gamelan scale). Laras pelog is played in the opening and closing songs while laras slendro is for songs in the middle. All the rhythms are metrical with medium speed and then high speed at the end of the songs. This speed arrangement forms a dramatic pattern of a single cone. The literary ornaments used are purwakanthi guru swara with rhyming scheme of a-a or a-aa The functions of Singiran in the context of tahlilan ritual are (a) as an Islamic propagating medium, and (b) as a means of tightening brotherhood among the members of tahlil groups. Key words: Singiran, tahlilan, Islamic traditional Javanese culture